2019
DOI: 10.3389/fimmu.2019.02403
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Features of Natural Killer Cells in Multiple Sclerosis

Abstract: Human cytomegalovirus (HCMV) has been recently related with a lower susceptibility to multiple sclerosis (MS). HCMV promotes an adaptive development of NK cells bearing the CD94/NKG2C receptor with a characteristic phenotypic and functional profile. NK cells are proposed to play an immunoregulatory role in MS, and expansion of the NKG2C(+) subset was recently associated with reduced disability progression. To further explore this issue, additional adaptive NK cell markers, i.e., downregulation of FcεRIγ chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 46 publications
(80 reference statements)
5
20
1
Order By: Relevance
“…Finally, a statistically significant correlation was also found between VCA IgG titers and the starting age, only among treated MS patients (negative correlation; Supplementary Table S4 ). Although EBV has been repeatedly associated with MS [ 2 , 9 , 65 ], and we have found statistically significant differences in the prevalence of EBNA-1 IgG between MS patients an HC, and in the EBNA-1 and VCA IgG titers between untreated MS patients and HC, we have not found any correlation between them and the other environmental factors, with the clinical variables analyzed or with the immune cells in our study. The only correlation found is the one mentioned above: higher VCA IgG titers were found in those MS patients with a lower age of onset.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Finally, a statistically significant correlation was also found between VCA IgG titers and the starting age, only among treated MS patients (negative correlation; Supplementary Table S4 ). Although EBV has been repeatedly associated with MS [ 2 , 9 , 65 ], and we have found statistically significant differences in the prevalence of EBNA-1 IgG between MS patients an HC, and in the EBNA-1 and VCA IgG titers between untreated MS patients and HC, we have not found any correlation between them and the other environmental factors, with the clinical variables analyzed or with the immune cells in our study. The only correlation found is the one mentioned above: higher VCA IgG titers were found in those MS patients with a lower age of onset.…”
Section: Discussioncontrasting
confidence: 85%
“…Thus, untreated MS patients showed significantly higher levels of HHV-6A/B IgG ( p = 0.0005), EBNA-1 IgG ( p = 0.0004), VCA IgG ( p = 0.010) and AA ( p = 0.011) in comparison with HC, but significantly lower levels of 25(OH) ( p = 0.007) and a significant decrease of the PA/AA and BA/AA ratios ( p < 0.0001 in both cases). These results would support the possible involvement of these viruses, the vitamin D and the SCFAs in MS etiopathogenesis, as it has been widely published in recent years [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. When we analyzed their possible correlations, we found differences between HC and MS patients.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The increase of clonally expanded CD8 T cells and of anti-CMV antibodies associate with immunosenescence ( 12 ). In addition, CMV infection occurs more frequently in older individuals in MS and associates with lower production of pro-inflammatory cytokines and ( 36 , 37 ). These data show that M- patients show an early immunosenescence process associated with a down-regulation of the pro-inflammatory adaptive immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The antiviral function of CD56 dim NK cells may be important in controlling MS. CD56 dim NK cells are involved in the immune response against infection by cytomegalovirus (CMV), and such an infection is associated with a lower risk of developing MS. A recent study showed that NK cells from patients with progressive MS, and particularly, primary progressive MS, have lower effector function towards target cells; the authors speculate that this might contribute to lower capability of killing viruses such as the Epstein-Barr virus, which may be involved in MS pathogenesis [27]. Others hypothesize that CD56 dim NK cells could be detrimental: increased numbers of CD56 dim NK cells expressing perforin have been found in patients with secondary progressive MS [28].…”
Section: Nk Cells In Untreated Ms Patientsmentioning
confidence: 99%